Mapping research trends in physical education pedagogies: a bibliometric analysis using scopus database - Gustian, Uray; Suherman, Adang; Yustiana, Yusi Rika; Erida, Megia; Malik, Arief Abdul; Rusmintaningsih, Fika Nuraini (Retos (Madrid), 2024)
This study aims to provide a comprehensive and systematic review of research trends in applying pedagogical models in physical education (PE) pedagogy. Furthermore, there are ongoing challenges facing teaching and learning in PE to deliver effective learning and achieve current learning objectives. This study used a bibliometric analysis approach by examining publication growth patterns, distribution of publication growth, distribution of authors, countries, affiliations, and network analysis based on the appearance of keywords. A search for articles in the Scopus database with specific keywords related to PE pedagogy yielded 419 relevant articles analyzed using CSV and VOSViewer applications. The results revealed a positive trend of increasing the number of published articles starting in 2018 and peaking in 2022. Keith Davids is a famous and influential author with the most publications and the highest citations. His article titled Algorithmic Skin: Health-tracking Technologies, Personal Analytics and the Biopedagogies of Digitized Health and Physical Education, written by Ben Williamson, was the most popular article with 123 citations. China has the most productive authors, and the United Kingdom is the country of origin for the most popular authors with the highest citation rates. The current and emerging trends demonstrate the integration of innovative teaching practices, alternative pedagogical approaches, and the promotion of holistic student development to cope with the development of PE. At the same time, the co-word analysis presents further research streams that include technology utilization and integrative approaches to transformative PE. In conclusion, this study has practical and theoretical implications in the research and practice of physical education pedagogies to identify integration and strategies and PE pedagogies. Keywords: physical education pedagogy; the trend of research; the integration of innovative and alternative pedagogical approaches; technology utilization and integrative approaches